An experimental investigation into the flow behaviour of submersibles. - Singh, Gurnihal (Nanyang Technological University, 2022)
Submarines are relatively complicated machinery that are required to operate in a range of environments and operations. To achieve efficient operations, as well as to maintain a strategic advantage, it is important to focus on the flow around the submarine, especially on the areas where the flow separates from laminar to turbulent regions.